Finding solutions to problems that never existed: a case study of co-creation in the municipality of the future - Anja K. Ruess; Ruth Müller (Journal of Responsible Innovation)
Over the past decade, co-creation, i.e. practices bringing together diverse actors to achieve mutually beneficial outcomes, has emerged as a broadly desired approach to innovation governance. Co-creation takes many shapes and its promises range from more successful innovations to more inclusive and responsible forms of innovating. In this paper, we interrogate co-creation practices by tracing how they shape techno-society relations through the inclusion of publics in smart city contexts. Our analysis focuses on an initiative that aimed to include citizens into the development of smart city technologies. Drawing on ethnographic fieldwork and qualitative interviews, we discuss the social dynamics of doing co-creation as establishing a distinct technology versus orienting innovation towards citizens’ needs, and show how pre-made commitments to particular technologies and stakeholders shape citizens’ agency. Understanding these dynamics will contribute to the growing debate about co-creation by providing a nuanced outlook on co-creative innovation practices, their potentials, and challenges.